2013
DOI: 10.1128/jcm.00871-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Diagnosis of Polycystic Echinococcosis Due to Echinococcus vogeli in a Paraguayan Immigrant in Argentina

Abstract: Polycystic echinococcosis due to Echinococcus vogeli is a rare parasitic infection that occurs in rural areas of Central and South America. Only molecular identification performed on formalin-fixed paraffin-embedded liver tissue samples gave an unequivocal diagnosis of this disease in a Paraguayan immigrant in Argentina.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…The most likely reason for this is a loss of DNA stability in conserved FFPE material, as has been previously described [ 38 ]. It has already been suggested that in such cases the application of shorter amplicons might lead to higher resolution [ 39 ] but at least in our case, the utilization of an amplicon of around 200 bp did not yield improved results. This does not exclude, however, that the utilization of alternative primers, shorter amplicons, or specific DNA purification methodology for FFPE material (e.g.…”
Section: Discussioncontrasting
confidence: 56%
See 1 more Smart Citation
“…The most likely reason for this is a loss of DNA stability in conserved FFPE material, as has been previously described [ 38 ]. It has already been suggested that in such cases the application of shorter amplicons might lead to higher resolution [ 39 ] but at least in our case, the utilization of an amplicon of around 200 bp did not yield improved results. This does not exclude, however, that the utilization of alternative primers, shorter amplicons, or specific DNA purification methodology for FFPE material (e.g.…”
Section: Discussioncontrasting
confidence: 56%
“…Since DNA degradation in FFPE samples of longer storage is most probably due to DNA fragmentation [ 38 ], the utilization of shorter amplicons up to 200 bp has been suggested as possible improvement [ 39 ]. We therefore designed another primer (12S-newR2) which, together with primer 12S-newF should amplify a fragment of 287 nt and tested this combination on isolated parasite cells mixed with 25 mg liver tissue of M .…”
Section: Resultsmentioning
confidence: 99%
“…(4) Another human case of infection but by E. vogeli was reported from Argentina, the female patient was a Paraguayan immigrant who presented jaundice and abdominal pain in the right hypochondriac region. The diagnosis was achieved by abdominal CT, immunodiagnosis techniques (ELISA, immunoelectophoresis, Western blot), histopathologic studies, and molecular techniques (PCR) [37]. On the contrary, a review was recently published on the genus Echinococcus spp.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the amplification of the above-mentioned sample SI-H4 at the rrnS locus was successful only when a shorter fragment of this gene was amplified. However, as discussed in previous studies, the use of a target size shorter than 200 bp might have increased the sensitivity even further [ 52 , 53 ]. An interesting approach was described in the study of Koonmee et al [ 52 ], where repeated PCR using the same primer sets and conditions was successfully employed for the amplification of short DNA fragments from formalin-fixed paraffin-embedded (FFPE) tissues.…”
Section: Discussionmentioning
confidence: 99%